Asymmetric synthesis of functionalized trifluoromethyl-substituted pyrrolidines via an organocatalytic domino Michael/Mannich [3+2] cycloaddition. Issue 97 (17th November 2016) - Zhi, Ying; Zhao, Kun; Liu, Qiang; Wang, Ai; Enders, Dieter
Abstract : The asymmetric synthesis of highly functionalized pyrrolidine derivatives with three contiguous stereogenic centers and bearing a trifluoromethyl group has been developed through an organocatalytic domino Michael/Mannich [3+2] cycloaddition sequence. Abstract : The asymmetric synthesis of highly functionalized pyrrolidine derivatives with three contiguous stereogenic centers and bearing a trifluoromethyl group has been developed through an organocatalytic domino Michael/Mannich [3+2] cycloaddition sequence. Employing a commercially available secondary amine as the catalyst, the scalable one-pot protocol occurs with high yields and excellent stereoselectivities, providing a short entry into a series of trifluoromethylated pyrrolidines with potential medical value.